Characteristics of successful performance support team members at the Olympic Games - Burns, L.; Stanimirovic, R.; Donaldson, A. (International Journal of Sports Science & Coaching, 2024)
Objectives Athletes and coaches rely on their performance support team to optimise training and competition. The specific characteristics of performance support teams that contribute to success in competition from the perspective of athletes and coaches have not been examined. Olympic gold medal winning athletes and coaches were asked about the characteristics they valued in the performance support team members who were with them at the Olympic Games. The insights shared provide important context to the role of the performance support team member, beyond technical skills, in the high-stress environment of elite sporting competition.